The Role of Employee Engagement in Enhancing Customer Experience in the Retail Sector - Evy Oktaviani Fauzi (Journal Of Resource Management, Economics And Business, 2025)
Purpose: This study aims to develop a conceptual model explaining how employee engagement influences customer experience (CX) in the retail industry, with service behavior serving as a mediating mechanism. It highlights the importance of frontline employees in shaping customer perceptions through their engagement and service behaviors. Research Methodology: The research adopts an integrative literature review approach, synthesizing theoretical and empirical studies from various disciplines. The study integrates the Service Profit Chain and Affective Events Theory to build the conceptual model. Results: The model suggests that emotionally engaged employees tend to exhibit proactive, empathetic, and responsive service behaviors, which, in turn, improve customer satisfaction and loyalty. The study proposes three theoretical propositions linking employee engagement to CX through service behavior. Limitations: The study is conceptual and relies on existing literature rather than empirical data. Future research is needed to validate the proposed model with quantitative studies or field experiments. The model also focuses primarily on frontline employees and does not address the role of back-office staff. Contribution: This research contributes to the theoretical understanding of the relationship between internal (employee engagement) and external (customer experience) factors in retail. It emphasizes the critical role of service behavior as a mediator and provides managerial implications for creating a human-centric retail strategy.